MANIFESTASI RONTGENOGRAFI DIABETES MELLITUS DI RONGGA MULUT - Trelia Boel (Faculty of Dentistry, Universitas Indonesia, 2015)
Diabetes mellitus is a common disease, described as a systemic disease of carbohydrate metabolism caused by a realtive or absolute deficiency of insulum. This condition is characterized by hyperglyecemia, glucosuria, polyuria, polydipsia, pruritis, and weight loss. Diabetes mellitus in itself does not cause periodontal disease, however diabetes or patients with an increased blood glucose concentration (>200mg/dl) tend to gave increased incidence and severity of periodontal disease. Patient with diabetics above 50 years old (3 cases) radiographically can be seen as alveolar bone loss in maxilla and mandible. Alveolar bone loss is seen larger in the posterior maxilla region. The vascular alteration in diabetics may enhance the susceptibility of periodontium to become periodontitis and serve as an etiology factor in pathologic bone resorption.